Synthesis, biophysical and biochemical studies of new guanidine-like derivatives targeting DNA - Nagle, Padraic Sean (Trinity College (Dublin, Ireland). School of Chemistry, 2010)
The literature describes many DNA minor groove binders, some of them having similar characteristics such as crescent shape, being dicationic and containing hydrogen bond donating or accepting groups.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.